Early life PCB138 exposure induces kidney injury secondary to hyperuricemia in male mice. (15th May 2022) - Ruan, Fengkai; Liu, Changqian; Hu, Weiping; Ruan, Jinpeng; Ding, Xiaoyan; Zhang, Lu; Yang, Chunyan; Zuo, Zhenghong; He, Chengyong; Huang, Jiyi
Abstract: Polychlorinated biphenyls (PCBs) are a class of persistent organic pollutants (POPs) that have adverse effects on human health. However, the long-term health effects and potential mechanism of neonatal exposure to PCBs are still unclear. In this study, nursing male mice exposed to PCB138 at 0.5, 5, and 50 μg/kg body weight (bw) from postnatal day (PND) 3 to PND 21 exhibited increased serum uric acid levels and liver uric acid synthase activity at 210 days of age. We also found an increased kidney somatic index in the 50 μg/kg group and kidney fibrosis in the 5 and 50 μg/kg groups. Mechanistically, PCB138 induced mitochondrial dysfunction and endoplasmic reticulum (ER) stress, which might have led to inflammatory responses, such as activation of the NF-κB (nuclear factor kappa-B) and NLRP3 (NOD-like receptor protein 3) pathways. The inflammatory response might regulate renal fibrosis and hypertrophy. In summary, this study reports a long-term effect of neonatal PCB exposure on uric acid metabolism and secondary nephrotoxicity and clarifies the underlying mechanism. Our work also indicates that early life pollutant exposure may be an important cause of diseases later in life. Graphical abstract: Image 1 Highlights: Early life PCB138 exposure can induce hyperuricemia in adult male mice. PCB138 can induce kidney hypertrophy and fibrosis secondary to hyperuricemia. Mitochondrial dysfunction and endoplasmic reticulum stress cause inflammation. Abstract : After exposure to PCB138 from postnatal day (PND) 3 to PND 21, male mice developed renal hyperuricaemia at 210 days, which may have contributed to mitochondrial dysfunction and ER stress, leading to inflammatory responses, renal fibrosis and hypertrophy.